π‐Extended Polyaromatic Hydrocarbons by Sustainable Alkyne Annulations through Double C−H/N−H Activation - Gońka, Elżbieta (Chemistry, 2019)
The widespread applications of substituted diketopyrrolopyrroles (DPPs) call for the development of efficient methods for their modular assembly. Herein, we present a π‐expansion strategy for polyaromatic hydrocarbons (PAHs) by C−H activation in a sustainable fashion. Thus, twofold C−H/N‐H activations were accomplished by versatile ruthenium(II)carboxylate catalysis, providing step‐economical access to diversely decorated fluorogenic DPPs that was merged with late‐stage palladium‐catalyzed C−H arylation on the thus‐assembled DPP motif.